Comparison of cutout risk factors between single- and doublescrew proximal nails in intertrochanteric femur fractures - a multicentric study - Giulia Colasuonno; Vincenzo Caiaffa; Giuseppe Solarino; Michele Coviello; Antonella Abate; Giovanni Vicenti; Francesco Ippolito; Vittorio Nappi; Andrea Michele Abbaticchio; Elio Caiaffa (Medicinski glasnik, 2023)
Aim: Significant risk factors for femoral nail cutout are well-documented, primarily in the context of single-screw proximal nails. However, it remains uncertain whether those same risk factors are applicable when considering different implant devices. The aim of this retrospective cohort study was to compare cutout risk factors between single- versus double-screw proximal femoral nails. Methods: Patients over the age of 75 with intertrochanteric femur fractures (AO Classification 31-A1 or 31-A2) were included in the multicentre study. A study group was treated with a double-screw nail, while a control group received single-screw device. Demographic data, surgical time (min), fracture pattern, distal locking, reduction quality, comorbidities, tip-apex distance (TAD) and 12-month functional scores was collected. Results: Two hundred patients were enrolled, 100 for each group. Nine patients experienced a cutout complication, five in the study and four in the control group. The main differences were in distal locking configurations (p<0.05) and in TAD values (p<0.05). The TAD value was higher in the study than in the control group (30.40±0.89 versus 26.79±1.79). No differences at 12-month follow up were reported according to functional scores. Conclusion: This study provides insights into the choice of nail systems for intertrochanteric femur fractures, highlighting the importance of distal locking configurations and TAD values. The double screw nail exhibits quite a tolerance by having a higher average TAD value. These findings may guide clinical decisionmaking in the treatment of this challenging fracture type.
Keywords: internal fixation; nailing; postoperative complication; proximal femoral fractures